2004
DOI: 10.1161/01.str.0000121648.74433.b5
|View full text |Cite
|
Sign up to set email alerts
|

Prescription of Antithrombotic Therapy in Older Patients Hospitalized for Transient Ischemic Attack and Ischemic Stroke: The GIFA Study

Abstract: Background and Purpose-Antithrombotic therapy has been demonstrated as an effective tool for secondary ischemic stroke prevention. Nevertheless, scant data are available on actual prescription of this therapy in clinical practice. Methods-A total of 17 337 patients admitted to geriatric and internal medicine wards participating in the study in the 1993 to 1998 survey period were analyzed. Patients with coded diagnoses of ischemic stroke and transient ischemic attack (TIA) were selected. Data recorded included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 33 publications
4
24
0
1
Order By: Relevance
“…11 Also, in an Italian study of hospitalized TIA and ischemic stroke patients, more than 40% were discharged without any antithrombotic medication. 26 We also found that patients who were given aspirin in our study were less likely to be admitted (OR, 0.2). Although our data do not allow us to know the reason for this, we speculate that physicians who discharged TIA patients felt a need to ''do something,'' and thus prescribed aspirin.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…11 Also, in an Italian study of hospitalized TIA and ischemic stroke patients, more than 40% were discharged without any antithrombotic medication. 26 We also found that patients who were given aspirin in our study were less likely to be admitted (OR, 0.2). Although our data do not allow us to know the reason for this, we speculate that physicians who discharged TIA patients felt a need to ''do something,'' and thus prescribed aspirin.…”
Section: Discussionsupporting
confidence: 61%
“…2 Both the AHA 18-21 and NSA 22 have disseminated guidelines for the approach to TIA patients. Because compliance with these recommendations is highly variable, 11,[23][24][25][26] we studied this issue in TIA patients seen in U.S. EDs. We focused on three elements: use of brain imaging, administration of antiplatelet agents, and hospitalization rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with the results of our study, Volpato et al (23) found a considerably high rate (more than 40 %) of patients with acute ischemic stroke or TIA without prescription of antithrombotic therapy at hospital discharge. In a cross-sectional survey carried out by Filippi et al (11), in family practice more than one quarter of patients with a history of stroke or TIA were not treated with antithrombotic agents.…”
Section: Tab 2 the Univariate Analysis Of The Infl Uence Of Patientsupporting
confidence: 93%